IMPLIKASI PERUBAHAN KURIKULUM PENDIDIKAN PADA SISTEM PENDIDIKAN TARUNA TERHADAP PENCAPAIAN KUALITAS TARUNA GUNA MENDUKUNG KETAHANAN SATUAN (STUDI DI AKADEMI MILITER MAGELANG JAWA TENGAH) - , Rita Kuntarti ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research was conducted at the Military Academy Magelang in Central Java. Military Academy as an educational institution soldiers and officers have an important role in the preparation of strategic human resource officers of Army soldiers are professionals, always follow the changes and dynamics according to the needs and development of education . Manifestations been implemented through the efforts of soldiers in an integrated development , (sustainable ) and consistent. Change of competence curriculum Military Academy Diploma ( D - 3) into the Diploma - 4 which has two competency as officer Lieutenant - ranking officers and a Bachelor of Applied Defense Sains . To meet the challenges of change, then there should be a change in the pattern of education to change the implementation of the curriculum as stated in No. Perkasad / 8/V/2009 dated May 19, 2009 on the Military Academy Education Curriculum , a pattern of 4 years of education . The background is done with the title research âChanger 's Implication Curriculum Education System on the Quality Cadet Midshipman To Support Security Unitâ. The purpose of this research was to determine the impact implication of changes in the educational curriculum in the education system towards the achievement quality Midshipman Military Academy as well as to determine the impact of changes in the educational curriculum in the education system towards achieving quality for the resistance unit. This is a descriptive qualitative research , meaning research that attempted to describe in detail the socio-cultural phenomena that occur in the community . Data extraction technique by using purposive sampling and snowball sampling. It is on the basis that the informant has been estimated data needed to answer the research problem and also has the authority to provide the information. The results of research indicating that the model curriculum affects the quality of education output and competence of the Military Academy . Further design curricula also have a significant impact on both the level of resistance of the internal units Military Academy. The conclusion that curriculum change is indeed very important, but it should provisions of a procedural nature. The curriculum needs to be reviewed in the content, load and implementation activities. Military material to provide a more focused character education that is contextually specific defense, the intensity of activities cadets need to be reviewed, but it requires awareness and commitment from all levels in order to have the same perception that, however great the cadets still have limitations both physically and psychogical.